2010
DOI: 10.1111/j.1742-4658.2010.07811.x
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic control of anhydrobiosis‐related accumulation of trehalose in the sleeping chironomid, Polypedilum vanderplanki

Abstract: Larvae of an anhydrobiotic insect, Polypedilum vanderplanki, accumulate very large amounts of trehalose as a compatible solute on desiccation, but the molecular mechanisms underlying this accumulation are unclear. We therefore isolated the genes coding for trehalose metabolism enzymes, i.e. trehalose-6-phosphate synthase (TPS) and trehalose-6-phosphate phosphatase (TPP) for the synthesis step, and trehalase (TREH) for the degradation step. Although computational prediction indicated that the alternative splici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 58 publications
2
60
0
Order By: Relevance
“…In some invertebrates, desiccation tolerance is attributed to the presence of oligosaccharides, mainly trehalose (Crowe, 2002;Sakurai et al, 2008;Mitsumasu et al, 2010;Tyson et al, 2012), which protect cell membrane integrity during dehydration and rehydration (Clegg, 2001), probably by organic glass formation in the dry state (Burke, 1986;Crowe et al, 1998). Other oligosaccharides such as sucrose, cellobiose or melibiose protect the activity of freezedried β-galactosidase (Heljo et al, 2011).…”
Section: A Role For Ar-cba-1 In Anhydrobiosis?mentioning
confidence: 98%
“…In some invertebrates, desiccation tolerance is attributed to the presence of oligosaccharides, mainly trehalose (Crowe, 2002;Sakurai et al, 2008;Mitsumasu et al, 2010;Tyson et al, 2012), which protect cell membrane integrity during dehydration and rehydration (Clegg, 2001), probably by organic glass formation in the dry state (Burke, 1986;Crowe et al, 1998). Other oligosaccharides such as sucrose, cellobiose or melibiose protect the activity of freezedried β-galactosidase (Heljo et al, 2011).…”
Section: A Role For Ar-cba-1 In Anhydrobiosis?mentioning
confidence: 98%
“…These enzyme's activities increased during dehydration, whereas that of trehalase decreased. This was not only due to altered enzymatic activity, but also to transcriptional control, as the levels of the synthesis enzymes cDNAs increased at the beginning of dehydration, whereas that of trehalase increased only after forty eight hours since inititation of dehydration, perhaps as preparation for subsequent rehydration [63]. Other species also use trehalose as a protectant during anhydrobiosis: the crustacean Artemia salina and the nematode Avelenchus avenae.…”
Section: Anhydrobiosismentioning
confidence: 99%
“…6). Functional and expression analyses showed that trehalose was abundantly synthesized as consistent with increased activities of TPS and TPP and suppressed TREH activity (70).…”
Section: Trehalosementioning
confidence: 99%